Seepage Analysis and Optimization of Reservoir Earthen Embankment with Double Textured HDPE Geo-Membrane Barrier - Kennedy C. Onyelowe; Akash Nimbalkar; Narala G. Reddy; Jair de Jesus A. Baldovino; Shadi Hanandeh; Ahmed M. Ebid (Salehan Institute of Higher Education, 2023)
This research paper focuses on conducting a steady state seepage analysis along with the downstream slope factor of safety using the Modified Bishops method in a poorly compacted earthen embankment and optimizing the same reservoir earthen embankment in a case study located near Sadiyavav village in Junagadh district in Gujarat, India. The study site, situated at 21°32'06.5